1994
DOI: 10.1146/annurev.pu.15.050194.001223
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Research on the Etiology of Injuries at Work

Abstract: INTRODUCTIONDuring the past half century, traumatic injuries have emerged as a pre-em inent public health challenge. Injury is the leading cause of hospitalization and death in persons younger than 45 years of age; results in more years of potential life lost than cancer or heart disease; and is second only to respiratory conditions as a reason for contact with physicians (3). One third of all nonfatal injuries and one sixth of all injury fatalities among adults aged 20 to 64 occur on the job (3).The public he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1
4

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 40 publications
2
36
1
4
Order By: Relevance
“…Posteriormente, realizou-se a análise multivariada somente para os trabalhadores industriais, e os resultados foram similares. (Veazie, 1994). No entanto, estudos de casos e controles estão sujeitos a uma série de possíveis vieses: * para renda e escolaridade(em todos os grupos-controle) e também para idade e cor (controles de trabalho) ** procurando emprego, insatisfeito com chefe, insatisfeito com salário e hostilidade no emprego.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Posteriormente, realizou-se a análise multivariada somente para os trabalhadores industriais, e os resultados foram similares. (Veazie, 1994). No entanto, estudos de casos e controles estão sujeitos a uma série de possíveis vieses: * para renda e escolaridade(em todos os grupos-controle) e também para idade e cor (controles de trabalho) ** procurando emprego, insatisfeito com chefe, insatisfeito com salário e hostilidade no emprego.…”
Section: Resultsunclassified
“…A idade tem sido um dos fatores de risco mais estudados (Veazie, 1994), sendo os resultados controversos (Laflamme, 1995). Os resultados da Tabela 2 mostram que os trabalhadores com mais de trinta anos tiveram duas vezes mais risco de acidentar-se.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Selfreported measures have been effectively used in accident and safety analyses (e.g., Gyekye, 2005Gyekye, , 2006Siu et al, 2003). Besides, while epidemiologic reports have been found to be faulty, biased and deficient because of poor documentation (Parker et al, 1994;Veazie et al, 1994), research reports have found self-reported accident rates to be closely related to documented accident rates (Smith et al, 2001). Notwithstanding the above-mentioned limitation, the current study contributes to the growing body of research which has identified educational status as important variable for investigation in safety management policies.…”
Section: Safety Implications and Directions For Further Studiesmentioning
confidence: 99%
“…Ampla revisão bibliográfica revelou grande número de artigos descritivos, mas foi reduzido o número de referências sobre as cargas de trabalho e o risco de acidentes. Conforme revisão realizada por Veazie et al 21 O presente estudo utilizou o delineamento de casos e controles para investigar a associação entre a exposição às cargas de trabalho, verificada através da percepção dos trabalhadores, e os acidentes de trabalho notificados em Pelotas. Para cada caso foram selecionados três controles: um trabalhador da mesma empresa, um vizinho do acidentado e um controle populacional.…”
Section: Introductionunclassified